STABILITY IN PRODUCTION PROCESS OF TRANSPORT MACHINERY - T. I. Chepeleva (Наука и техника)
The paper presents a mathematical model of stable production system for transport machinery. A detailed functional structure with various functions and sub-functions where some functions are considered as insignificant from the point of view of production transformations has been built in accordance with the construction diagram. The production structure with the fixed constructive characteristics has been obtained in the paper. Output actions in such production system are assigned by specific transformation technologies where an action method is determined by place, character of production process actions and conditions of its accomplishment. Number of constructive characteristics are determined by functional structure and depend on an abstraction rate, revealing ratio of complete description of the production system.